Enzymatic post-translational modifications of proteins in chronic kidney disease: mechanisms, regulation, and clinical significance - Wei, Minlong; Lin, Jinyun; Zeng, Yi; Wang, Xiaojuan; Wen, Jialu; Wang, Jing; Zou, Wei; Tu, Kang; Liu, Menghua; Li, Juan (Frontiers in Pharmacology, 2025)
Chronic kidney disease (CKD) involves intricate pathological mechanisms that currently lack definitive therapeutic interventions to halt disease progression. Increasing evidence suggests that enzymatic post-translational modifications (ePTMs) of proteins play an important role in CKD. As a dynamic and reversible type of PTM, ePTMs offer advantages such as enzyme-specific catalysis, high reversibility, and precise regulation. Various forms of ePTMs have been reported in CKD, including methylation, acetylation, ubiquitination, enzymatic glycosylation, lactylation, palmitoylation, crotonylation, SUMOylation, and prenylation. Given the critical roles of these ePTMs in CKD, this review summarizes their molecular mechanisms in disease progression, explores their potential as diagnostic markers and therapeutic targets, and highlights advances in small-molecule drugs targeting ePTMs. It is important to note that most ePTMs remain in the early stages of research, with evidence of cross-regulation and synergistic effects among different modifications. Further investigation will require more basic studies and clinical trials. This review aims to help bridge the gap between basic research and clinical application of ePTMs in CKD, and to support the development of more effective treatment strategies.